Comparison of Chemical and Interpretative Methods: the Carbon–Boron π‐Bond as a Test Case. Issue 71 (23rd November 2020) - Gupta, Radhika; Rezabal, Elixabete; Hasrack, Golshid; Frison, Gilles
Abstract: Quantum chemical calculations and NBO, ETS‐NOCV, QTAIM and ELF interpretative approaches have been carried out on C‐donor ligand‐stabilized dihydrido borenium cations. Numerous descriptors of the C−B π‐bond strength obtained from orbital localization, energy partitioning or topological methods as well as from structural and chemical parameters have been calculated for 39 C‐donor ligands including N ‐heterocyclic carbenes and carbones. Comparison of the results allows the identification of relative and absolute descriptors of the π interaction. For both families of descriptors excellent correlations are obtained. This enables the establishment of a π‐donation capability scale and shows that the interpretative methods, despite their conceptual differences, describe the same chemical properties. These results also reveal noticeable shortcomings in these popular methods, and some precautions that need to be taken to interpret their results adequately. Abstract : π‐Bond quantification : Using relevant molecular descriptors is the key to describe the electronic structure. Their comparison was conducted for the πCB ‐bond of carbene–borenium complexes, revealing the carbene π‐donating capability and the strengths and weaknesses of the NBO, ETS‐NOCV, QTAIM and ELF methods.